Processing and Properties of AlCoCrFeNi High Entropy Alloys: A Review. (3rd October 2022) - Gopal, P.M.; Soorya Prakash, K.; Kavimani, V.; Rajendiran, Gopal
Abstract : The aim of this study is to carry out a focused literature review on the mechanical and tribological behaviour of AlCoCrFeNi High Entropy Alloys (HEA). HEAs are a proficient class of alloys designed by the use of several constituent alloying elements in equiatomic or close to equiatomic ratios. In view of their distinctive property range, there has been huge attention on this class of alloys. Among the various group of HEAs, AlCoCrFeNi-based HEAs have attracted interest due to their enhanced properties. Various AlCoCrFeNi-based HEAs are developed by adding additional elements such as Mo, Ti, and Zr. The effect of these alloying constituents on the mechanical, metallurgical, and tribological performance of the AlCoCrFeNi HEA is discussed in detail. In addition to that, the various techniques used to produce these HEAs are also discussed.